Factors that influence organizational citizenship behavior - Irfanesa, Irfanesa; Darmawan, Akhmad; Aryoko, Yudhistira Pradhipta; Randikaparsa, Irawan (Institute of Computer Science (IOCS), 2024)
The purpose of this research is to determine the influence of transformational leadership style, work life balance and job satisfaction on organizational citizenship behavior (OCB) in nurses at Muhammadiyah Mardhatillah Randudongkal Hospital. This type of research is quantitative with a sample of 105 nurses. The sampling technique used was non-probability sampling with a saturated sampling approach. The analysis method uses Smart PLS version 4.0. Based on the research results, several conclusions are obtained: Transformational Leadership Style (X1) has a positive and insignificant effect on Organizational Citizenship Behavior (Y), Work life balance (X2) has a positive asnd significant effect on Organizational Citizenship Behavior (Y) , Job Satisfaction (X3) has a positive and insignificant effect on Organizational Citizenship Behavior (Y). The results of this researcher show that transformational leadership style and job satisfaction have a positive and insignificant influence on organizational citizenship behavior. Therefore, further research could add other variables to strengthen the relationship between transformational leadership style, job satisfaction and organizational citizenship behavior. It is hoped that these findings will provide insight for nurses at the Muhammadiyah Mardhatillah Randudongkal Hospital in improving OCB through developing appropriate policies